Using The Herringbone Technique to Improve Students’ Reading Achievement - Titik Hindrayani; Diah Ambarumi Munawaroh (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study examined how the herringbone technique was used to improve students' reading abilities in narrative text. This study used Classroom Action Research (CAR). The study is divided into two cycles. Two meetings were held during each cycle. The students’ reading comprehension value in cycle 1 did not meet the success criteria. Only 8 out of 24 students (66.7%) met the success requirements. Therefore, the researchers updated their strategy and moved on to the next cycle. The average value of students increased in cycle 2. All students got good grades, while no one got a negative score. In conclusion, the herringbone method used in class X at MTsN 1 Batu was able to improve students' ability to read narrative material